(untitled) (Journal of Intellectual Property Rights (JIPR), 2024)
India does not have a separate legislation for trade secret protection and moreover has been following the UK model for trade secret protection. Many of the Indian courts have cited English decisions in their judgements. The National Innovation Bill, 2008 was an effort initiated by the Ministry of Science and Technology to create a legislation with respect to protection of confidential information, however it was not tabled in the Parliament. A need for a separate law for trade secret protection was identified in the 161st Report on Review of the Intellectual Property Rights Regime in India of the Parliamentary Committee, where it was observed that there is lack of clarity on several aspects in the current framework of protecting trade secrets in India. One of the important inquiries to be undertaken is whether there is a dire need in the Indian industry for a legislation. Hence, an empirical study was carried out to understand the trade secret practices adopted by the Indian industry. For this purpose, a limited case study about industrial practices relating to trade secret protection in the Ayurveda industry was conducted. Empirical evidence shows that even though the industry is actively indulging in trade secrecy, the contribution of the current legal mechanism in this regard is very minimal. The industry experience strongly suggests that there is no need for a separate legislation.